The Impact of the Petroleum Prıce Reductıons on the Economıes of the Central Asıan Turkısh Communıtıes - Çamurdan, Burak (European Scientific Journal, ESJ, 2017)
The prices of Petroleum as the inevitable natural source of energy for all economies all over the World for years have been highly effecting those economies being in a serious fluctuation within the last 15 years. While its price was about per barell USD.20.- as of 2002, it had a pick at the level of USD.147.- during July 2008 by a rapid rise but it fell down again to level of 2009 at USD.35.- following the global crisis of 2008. However, between the years of 2011-2014 the prices, by gathering, had fluctuated in between the coridor of USD. 80-126. At the end of 2015, the price of WTI ( Teksas Petroleum) seriously decreased at the level of February 2009, down to USD.35,47 per barell. In parallel to WTI price, The Brent Oil price decreased down to USD.38,15 as well. Thereupon, as per these price fluctuations, most of the countries of which income sources mostly bound to these energy products have been facing vital economic problems. One of these countries is CIS (Russia). As CIS had been negatively effected by these oil price fluctuations, its sister countries which have historical and strict political and business relations were dragged to economic impasse. Not only, the position of CIS economy, but also the dramatic and ongoing price decreases related with the main income sources of the Central-Asian Turkish Communities forwarded their economies in problems by direct effects. Finally, the said economies have still been suffering from this problematic situation and have been trying to recover and to get rid of it. Through out this study, based on the OECD datas, it was found out that the Central-Asian Turkish Countries are urgently in need of new income sources other than the recent ones. If they couldn’t manage to find a way or the oil and natural gas prices couldn’t recover and reach to 2011-2014 period levels permanently, the collapses in those economies will be the inevitable fate in accordance with the general projections.